A seasonal comparison of prokaryote numbers, biomass and heterotrophic productivity in waters of the KwaZulu-Natal Bight, South Africa. (1st June 2016) - Muir, D; Kunnen, T; Scharler, UM
Abstract : The KwaZulu-Natal Bight is a shallow indentation of the eastern seaboard of South Africa, characterised by a narrow (45 km wide) extension of the continental shelf, with a shelf break at about 100 m. It has a complex hydrography: the waters of the bight are derived from the fast-flowing, southward-trending Agulhas Current, which is fed mostly by the tropical and subtropical surface waters of the South-West Indian Ocean subgyre, which are generally oligotrophic in nature, notably depleted in reduced nitrogen and phosphate except at river mouths and during periodic upwelling of deeper nutrient-rich water. Despite this, the bight is believed to be relatively productive, and it is suggested that efficient nutrient recycling by prokaryotes may sustain primary productivity efficiently, even in the absence of new nutrient inputs. Here we have measured bacterial numbers, biomass and heterotrophic productivity during summer and winter in conjunction with phytoplankton standing stock and factors that influence it. Bacterial distribution closely matched phytoplankton distribution in surface waters, and was highest close to the coast. Bacterial standing stocks were similar to those of oligotrophic systems elsewhere (0.5–5.0 × 10 5 cells ml –1 ; 1 × 10 –8 to 1.25 × 10 –7 g C ml –1 ) and increased in association with the development of phytoplankton blooms offshore and with inputs of allochthonous material by rivers at the coast. Heterotrophic productivity in summer was lowest in the far south and north of the bight (0.5 × 10 –10 g C ml –1 h –1 ) but higher close to the shore, over shallow banks, and in association with increased phytoplankton abundance over the midshelf (1.0–3.5 × 10 –9 g C ml –1 h –1 ). There were marked seasonal differences with lower bacterial standing stocks (5 × 10 4 to 2 × 10 5 cells ml –1 ; 4–5 × 10 –9 to 1–2 × 10 –8 g C ml –1 ) and very low bacterial productivity (4 × 10 –11 to 1 × 10 –10 g C ml –1 h –1 ) in winter, probably resulting from lowered rates of primary productivity and dissolved organic matter release as well as reduced riverine allochthonous inputs during the winter drought.